The Impact of Former European Prisoners of North Africa on their Community - ELBEY, Omar (My University, 2019)
During the early modern period, English seamen and merchants sailing to the Mediterranean were subject to attack by Muslim privateers who attempted to seize their cargo and carry their crew to the slave markets of North Africa. After being sold into slavery, some prisoners escaped, ransom payments gave others freedom, some converted to the Muslim faith, and more remained in captivity for years. A few of those who returned to England recounted their experiences in printed narratives that entertained and informed British readers. These exciting narratives recount the experiences of Englishmen abducted by the Barbary pirates of North Africa. After being sold into slavery, the narrators succeeded in returning to their homeland where their stories were printed. Never before available in a modern, annotated edition, these tales describe combat at sea, extraordinary escapes, and religious conversion, but they also illustrate the power, prosperity, and piety of Muslims in the early modern Mediterranean.
Case study English Prisoners (1580-1830)
Keywords: English seamen; Barbary pirates; Prisoners; Ransom; Muslim faith; Narratives